"YOU Were Adopted?!": Microaggressions Toward Adolescent Adopted Individuals in Same-Race Families. (April 2015) - Garber, Karin J.; Grotevant, Harold D.
This study delineated a microaggressions typology and corresponding intensity levels that occur to adopted adolescents. The microaggressions framework by Sue et al. was adapted to identify this adoptive microaggression typology. Interviews with 153 (males = 79, females = 74) non-Latino/a White adolescent adopted individuals in same-race families were analyzed. Thematic analysis was used to discover 16 themes: (a) Silence, (b) Overly Intrusive Questions, (c) Assumption of Bionormativity, (d) Recurring Confusion/Ignorance, (e) In-House Divisions, (f) Public "Outing, " (g) Using Adoption, (h) Questioning Authenticity, (i) Unacknowledged Identity Status, (j) Spokesperson for Adoption, (k) Adoptees as Nonnormative, (l) Sensitivity, (m) Negative Stereotypes about Birth parents, (n) Adoptees as Orphans, (o) Negative Societal Portrayal of Adoption, and (p) Other. Implications for theory and practice are provided.